Compendium of Guide Points, Schedules, Questionnaires and Instructions on the Study of Panchayati Raj - Planning Commission (Planning Commission, 1970)
As a first stop to the preparation of this Compendium, a working paper on Panchayati Raj was prepared, by the Project Director. This paper was discussed with the Planning Commission, the Ministry of Food and Agriculture, Community Development and Panchayati Raj and the All India Panchayat Parishad. The objectives of the study wore finalised after a careful consideration of the points raised at these discussions and a draft compendium prepared containing the schedules, guide -points, questionnaires etc., and instructions for collecting the relevant information. This compendium was circulated among all the field officers of the Programme Evaluation Organisation and their comments invited in the light of the field situation.
Programme Evaluation Organisation Planning Commission Government of India